A molecular perspective on the ageing of marine dissolved organic matter - R. Flerus; O. J. Lechtenfeld; B. P. Koch; S. L. McCallister; P. Schmitt-Kopplin; R. Benner; K. Kaiser; G. Kattner (Biogeosciences, 2012)
Dissolved organic matter (DOM) was extracted by solid-phase extraction (SPE) from 137 water samples from different climate zones and different depths along an eastern Atlantic Ocean transect. The extracts were analyzed with Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) with electrospray ionization (ESI). Δ14C analyses were performed on subsamples of the SPE-DOM. In addition, the amount of dissolved organic carbon was determined for all water and SPE-DOM samples as well as the yield of amino sugars for selected samples. Linear correlations were observed between the magnitudes of 43 % of the FT-ICR mass peaks and the extract Δ14C values. Decreasing SPE-DOM Δ14C values went along with a shift in the molecular composition to higher average masses (m/z) and lower hydrogen/carbon (H/C) ratios. The correlation was used to model the SPE-DOM Δ14C distribution for all 137 samples. Based on single mass peaks, a degradation index (IDEG) was developed to compare the degradation state of marine SPE-DOM samples analyzed with FT-ICR MS. A correlation between Δ14C, IDEG, DOC values and amino sugar yield supports that SPE-DOM analyzed with FT-ICR MS reflects trends of bulk DOM. DOM weighted normalized mass peak magnitudes were used to compare aged and recent SPE-DOM on a semi-quantitative molecular basis. The magnitude comparison showed a continuum of different degradation rates for the detected compounds. A high proportion of the compounds should persist, possibly modified by partial degradation, in the course of thermohaline circulation. Prokaryotic (bacterial) production, transformation and accumulation of this very stable DOM occur primarily in the upper ocean. This DOM is an important contribution to very old DOM, showing that production and degradation are dynamic processes.